Uncovering common disease mechanisms and critical biomarkers in Crohn’s disease with concurrent psoriasis and exploring potential therapeutic agents - Tianqi Liu; Xiaoqing Zhang; Ruiqi Chen; Yifan Sun; Ruijian Zhang; Liwen Zhang; Zhepeng Luo; Jiani Wang (PLoS ONE, 2025)
Introduction Research findings show a substantial correlation between Crohn’s disease and psoriasis. However, the exact cause or pathogenesis of the concurrent manifestations of these two conditions in the same individuals remains uncertain. This research aimed to scrutinize the important molecules and mechanisms responsible for the concomitance of Crohn’s disease and Psoriasis by using quantitative bioinformatics utilizing a publicly available RNA sequencing repository. Methods The database Gene Expression Omnibus were assessed, specifically for Crohn’s disease (GSE95095) and psoriasis (GSE13355). The ‘limma’ library of the R programming syntax is employed to identify differentially expressed genes. The Search Tool for Interacting Genes dataset was utilized to study the interaction between proteins networks. The Cytoscape software was utilized to efficiently view and analyse these Protein-Protein Interaction networks. The ctoHubba Cytoscape plugin helps in the selection of hub genes. These hub genes have been confirmed using data from GSE102133 for Crohn’s disease and GSE14905 for psoriasis. The ROC curves were utilized in this study to assess the diagnostic value of the hub genes. Moreover, new research involving gene-set enriched studies and the study of immunological surveillance associated with these specific genes is attainable. Results Among the identified common DEGs, 40 genes were downregulated and 37 were upregulated, totaling 77 genes. Crohn’s disease and Psoriasis had a higher concentration of pathways associated with inflammation. After validation, functionality of hub genes was confirmed for S100A12, CXCL8, IL1RN, S100A9, CXCL10, MMP1, CXCL1, FPR1, CXCR2, and S100A8. The hub genes showed an increase in expression in response to neutrophil infiltration. The expression of S100A12, CXCL8, IL1RN, S100A9, CXCL10, MMP1, CXCL1, FPR1, CXCR2, and S100A8 was found to be significantly linked to immune processes such as neutrophil activation, neutrophil chemotaxis, and neutrophil migration associated with Crohn’s and Psoriasis disease. Conclusions This bioinformatics study has elucidated S100A12, CXCL8, IL1RN, S100A9, CXCL10, MMP1, CXCL1, FPR1, CXCR2, and S100A8 as the central genes in the pathogenesis of CD and Psoriasis comorbidity. The significance of neutrophil infiltration in promoting inflammatory and immune-mediated dysfunction seems to be crucial in the etiology of concurrent Crohn’s and Psoriasis, offering an avenue for diagnostic and therapeutic methods.